2015
DOI: 10.1080/02786826.2015.1082532
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Powder Release Behavior from Capsule-Based Dry Powder Inhalers

Abstract: A methodology for studying the deagglomeration performance and emptying behavior of micronized mannitol powder from two commercial capsule-based dry powder inhalers (DPIs), the lowand high-resistance RS01 Ò , is presented. Mathematical modeling played a key role in the interpretation of the powder release behavior from these two DPI systems. Non-linear regression models, which were characterized from the aerosol obscuration versus time profiles obtained from laser diffraction particle sizing data, were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The aerosol performance of TPIP in the RS01 devices compares favorably to published data for other micronized and spray-dried powders. Huynh et al (2015) evaluated 20 mg micronized mannitol (median size of 5 µm) in the LR and HR devices. The ED for micronized mannitol was 73.8 and 72.5%, respectively, lower than that observed for all capsule doses of TPIP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aerosol performance of TPIP in the RS01 devices compares favorably to published data for other micronized and spray-dried powders. Huynh et al (2015) evaluated 20 mg micronized mannitol (median size of 5 µm) in the LR and HR devices. The ED for micronized mannitol was 73.8 and 72.5%, respectively, lower than that observed for all capsule doses of TPIP.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple RS01 device designs with varying resistances to airflow, and for the same inspiratory effort, the air flow rate will decrease as the device resistance increases. This enables the drug developer to select the device that most effectively disperses their powder formulation at an inspiratory effort that can be effectively achieved by their patient population (Huynh et al, 2015;Sahay et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Coates et al also demonstrated that reducing the inlet size of Aerolizer TM from full to one third also increased the axial velocity of the capsule, increased the capsule emptying rate and the amount of powder being emitted before full flow development, leading to 8% reduction in the FPF of mannitol. Huynh et al confirmed using laser obscuration (Spraytech) that the rate of powder emission from the capsule of the high resistance Osmohaler TM (smaller air inlet size) was marginally greater than the low resistance Osmohaler (larger air inlet size) (Huynh et al, 2015). This may help to explain the small 4% difference in FPF between the high (26% FPF) and low resistance (30% FPF) Osmohaler TM .…”
Section: Discussionmentioning
confidence: 87%
“…The observed flow dependency of particle size on the dispersion flow rates up to 120 L/min (for low resistance Osmohaler TM ) can be explained by Coates et al who reported that at higher dispersion flow rate of 120 L/min, a greater amount of powder can be emptied from the capsule before the full flow development (Coates et al, 2005;Huynh et al, 2015). This means less fraction of the emitted aerosol is de-agglomerated by the optimum turbulence and device-impaction energy level, leading to a less efficient powder deagglomeration and larger particle size distribution of the aerosol.…”
Section: Discussionmentioning
confidence: 88%
“…Relevant studies are still scarce in the literature, due to the complexity of the problem that includes the motion, physical state and emptying behaviour of capsule, as stated by Huynh et al [ 73 ]. Several issues have been identified, which may potentially affect their predicting capabilities of the available models.…”
Section: Review Of Up-to-date Dpi Modelling Studiesmentioning
confidence: 99%